Design of a effective DC-DC converter for solar energy conversion - Wu, Qingwang. (2011)
The global electrical energy consumption is rising and there is steady increase of the demand on power generation. So in addition to conventional power generation units a large no. of renewable energy units is being integrated into the power system. A solar energy system is the environmentally clean and safe renewable energy sources in world, more and more governments are supporting and developing it as well as the private sectors. The sunlight is not constant and even some times there is no sunlight, that’s why before the solar energy is called “alternative energy” because of the stability. Indeed the solar energy cannot be used directly if there is not controlled in the system. Our task is to develop a controlled system and make sure the wind turbine energy system is working safely, effectively to the end user and power grid.